Construction of ZnO@mSiO2 antibacterial nanocomposite for inhibition of microorganisms during Zea mays storage and improving the germination. (1st October 2022) - Zhang, Dong-Dong; Hu, Si; Wu, Qiong; Zhao, Jin-Feng; Su, Ke-Rui; Tan, Li-Qin; Zhou, Xian-Qing
Abstract: Zea mays (Maize) is prone to mildew due to its rich nutrition and large embryo, resulting in the decline of edible quality, germination rate and even threatening people's health. In this study, ZnO nanoparticles were prepared by hydrothermal method to inhibit the growth of microorganisms on the surface of Zea mays . For its safe and efficient application, mesoporous silica (mSiO2 ) was modified on its surface and successfully prepared ZnO@mSiO2 Nanocomposites. The ZnO@mSiO2 nanocomposites were successfully prepared and characterized by TEM, EDS, XRD, FT-IR, and it could significantly inhibit two model bacteria and three model fungi. After mixing with Zea mays and 42 days of simulated storage, they could significantly inhibit the growth of microorganisms in Zea mays, ensure the stability of Zea mays quality and improve the germination rate of Zea mays . The ZnO@mSiO2 nanocomposites prepared in this study provide a new idea for the safe storage of Zea mays . Graphical abstract: Image 1 Highlights: ZnO nanoparticles were prepared by hydrothermal method. Mesoporous silica coating was used to fix and isolate their contact with Zea mays . The prepared ZnO@mSiO2 could significantly inhibit the growth of bacteria and fungi. The ZnO@mSiO2 could improve germination rate of maize without damaging its quality.